Pengaruh Model Pembelajaran Students Teams Achievment Division (STAD) Berbantuan Wayang Kertas terhadap Motivasi Belajar dan Pemahaman Konsep Siswa Kelas II SD Negeri Gondoriyo Jambu - Safitri, Ayu Deni (Universitas PGRI Semarang, 2024)
The learning and learning process is a process that occurs in the educational unit environment. The learning process carried out must produce changes in the student's self, this is supported by the student's desire or encouragement to make changes in learning, this is called learning motivation. Motivation according to Sari (2018) is the desire from within oneself to carry out certain activities in order to achieve the goals to be achieved, Good motivation will later influence students' understanding of concepts. Jihad and Haris (2013) explain that conceptual understanding is a competency that enables students to understand concepts and carry out problem solving procedures accurately, efficiently and perfectly. The problem in this research is that teachers are not optimal in using learning media and only focus on the lecture method which causes students to get bored with learning and students' understanding of concepts is low, so the researcher offers a solution in the form of implementing the STAD learning model assisted by paper puppets. This research uses quantitative research with quasi-experimental research and nonequivalent control group design patterns, and data collection techniques through tests, observations, questionnaires and questionnaires, as well as documentation. The result is that H0 is rejected and Ha is accepted, meaning that there is a difference and influence in the application of the STAD learning model assisted by paper puppets on motivation of 72.3% and concept understanding of 61.9%. So, it can be concluded that the use of the STAD learning model assisted by paper puppet has an influence on students learning motivation and understanding of concepts.